Chapter Echi dell'Umanesimo-Rinascimento nell'Ucraina della prima modernità. Note a margine - Siedina, Giovanna (Biblioteca di Studi Slavistici, 2018)
In this article, after a short introduction, the author briefly illustrates certain particulars that have characterized the study of Humanism-Renaissance in Ukrainian literature, along with specific features in the development of Ukrainian literature that have determined a single Renaissance-Baroque stage, in which the Renaissance features were received and were developed in Baroque forms. At the same time, the author focuses on a few lines of study that will have to be examined in depth in order to gain greater knowledge and understanding about how Humanism and the Renaissance influenced the development of Ukrainian culture and literature.